Dedifferentiated transformation in metastatic liposarcoma of orbit and brain. (1st November 2020) - Kim, Sung Eun; Kim, Ji Hyun; Yang, Suk-Woo
ABSTRACT: A liposarcoma of the orbit is extremely rare and a metastatic liposarcoma of the orbit is even rarer. Histologically, metastatic tumors frequently resemble the appearance of the primary lesion or may be less differentiated. In the present paper, we report on a case of a metastatic liposarcoma of the orbit and brain in which dedifferentiated transformation occurred from the primary tumor. The primary liposarcoma was a myxoid liposarcoma in the thigh, which had been resected 6 years ago. The metastatic orbital liposarcoma was poorly differentiated compared to the primary tumor and the tumor in the brain was even more poorly differentiated and anaplastic than the tumor in orbit. The tumor in the orbit and brain was completely removed and postoperative radiotherapy and chemotherapy were performed.